Using Artificial Neural Networks for Designing of Electrical System for Buildings - ฤทธิ์ทอง, บัณฑิต; ศุภพิทักษ์สกุล, ฉัตรชัย (Frontiers in Engineering Innovation Research, 2009)
This paper proposes a novel technique for designing the electrical system of buildings using an Artificial Neural Network (ANN). The ANN is employed as a classifier for searching the data of the required electrical equipments in the data base which can help in saving time for estimating budget and planning for the electrical system installation. The data that obtained from the calculation according to the Electrical Installation Standard of Thailand are used as ANN training and testing sets. The data for an apartment as follows: types of the apartment, the apartment area (20-100 m2), air-condition system, electrical system (1 or 3 phase) are used as inputs of the ANN. The size of meter, circuit breaker, dimension of phase conductors, grounding conductors, metal conduits and the length of conductors are employed as output of the ANN. The satisfactory results were provided with a short time consuming although it was used by a new designer.